UN CIVILIAN POLICE : Efektivitas Kerja POLRI Pada Konflik Kamboja Tahun 1992-1993 - , Rian Ayu Fatria; , Drs. Samsu Rizal Panggabean, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia's participation in the UN peacekeeping mission resulted in success and get the highest award of the UN and the Cambodian government. With the persistence of armed conflicts in the world, the presence of Indonesian peacekeepers will remain an important and expected contribution in the future. UN police is an important tool used by organizations to help promote peace and security. Every day the UN Police strengthen and rebuild the security patrol, cooperate and act as advisors to the local police, help ensure compliance with international standards of human rights, and helping a variety of activities to restore and improve public safety and the rule of law. To that end, the UN Police in UNTAC should be fully committed to the mandate that has been given, although there are time constraints and limitations of expertation officers in the field. Commitment to maintaining basic mandate is key in restoring peace in conflict countries. Moreover minimize errors in working as peacekeeper is also very important to consider in order to create the ultimate peace in Cambodia. Keywords: Peace, Cambodian Conflict, Civil Police, United Nations, Mandate, Commitment.